Cytotoxic effects of Urtica dioica radix on human colon (HT29) and gastric (MKN45) cancer cells mediated through oxidative and apoptotic mechanisms - Ghasemi, S; Moradzadeh, M; Mousavi, S H; Sadeghnia, H R (Cellular and Molecular Biology, 2016)
Defects in the apoptotic pathways are responsible for both the colorectal cancer pathogenesis and resistance to therapy. In this study, we examined the level of cellular oxidants, cytotoxicity and apoptosis induced by hydroalcoholic extract of U. dioica radix (0-2000 µg/mL) and oxaliplatin (0-1000 µg/mL, as positive control) in human gastric (MKN45) and colon (HT29) cancer, as well as normal human foreskin fibroblast (HFF) cells. Exposure to U. dioica or oxaliplatin showed a concentration dependent suppression in cell survival with IC50 values of 24.7, 249.9 and 857.5 µg/mL for HT29, MKN45 and HFF cells after 72 h treatment, respectively. ROS formation and lipid peroxidation were also concentration-dependently increased following treatment with U. dioica, similar to oxaliplatin. In addition, the number of apoptotic cells significantly increased concomitantly with concentration of U. dioica as compared with control cells, which is similar to oxaliplatin and serum-deprived cancer cells. In conclusion, the present study demonstrated that U. dioica inhibited proliferation of gastric and colorectal cancer cells while posing no significant toxic effect on normal cells. U. dioica not only increased levels of oxidants, but also induced concomitant increase of apoptosis. The precise signaling pathway by which U. dioica induce apoptosis needs further research.